2017
DOI: 10.1515/eje-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Trends in High Nature Value farmland studies: A systematic review

Abstract: Background. Since the High Nature Value (HNV) concept was defined in the early 1990s, several studies on HNV farmland has been increasing over the past 30 years in Europe, highlighting the interest by scientific community of HNV farming systems supporting biodiversity conservation. The aim of this study was to evaluate the trends and main gaps on HNV farmland peer-reviewed publications in order to contribute to the effectiveness of future research in this field. Methods. Searches were conducted using the datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Such research typically focuses on the impacts of management practices on species communities, mostly species diversity (cf. Benedetti 2017). Studies on population genetics or genetic diversity are rare but might increase as cost of genetic analyses decreases (Plue et al 2019).…”
Section: Policy Drives the Research Agendamentioning
confidence: 99%
See 1 more Smart Citation
“…Such research typically focuses on the impacts of management practices on species communities, mostly species diversity (cf. Benedetti 2017). Studies on population genetics or genetic diversity are rare but might increase as cost of genetic analyses decreases (Plue et al 2019).…”
Section: Policy Drives the Research Agendamentioning
confidence: 99%
“…These have been and remain the predominant research topics in all boreal countries and probably across the EU. A recent review on high nature value farming similarly reported that biodiversity and conservation is the key research inquiry in over 50% of publications, followed by the third on agricultural policy (Benedetti 2017). Ecological studies are often accompanied by other research perspectives: most papers classified as multi-aspect studies combine ecology, management, land use change, and restoration.…”
Section: Research Into Semi-natural Habitats As Social-ecological Systemsmentioning
confidence: 99%
“…The sustainability of HNV farmland is equally important for the local communities and for the entire society due to its important cultural and environmental values [71]. For the next decades, the European Union established ambitious targets to tackle important environmental and climate challenges through the European Green Deal [72].…”
Section: Reflection On the Needs To Foster The Sustainability Of Hnv Farmlandmentioning
confidence: 99%
“…provide varied habitats for many wild plants and animals. Biodiversity on farmlands has been declining throughout Europe as a result of intensification of agriculture and abandonment of marginal lands since the second half of the 20th century (Keenleyside et al 2014;Lomba et al 2014;Benedetti 2017). Due to increasing awareness regarding the declining biodiversity on farmlands, the term High Nature Value farmland (HNVf) has become established (Beaufoy et al 1994;Andersen et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…HNV farming systems support the existence of agriculture-dependent species and their habitat, as they are low-intensity farming systems (Lomba et al 2014(Lomba et al , 2015(Lomba et al , 2017. HNVf is characterized based on the proportion of semi-natural vegetation and the extent of permanently or periodically uncultivated landscape elements in farmland; the density of livestock; and the input of nutrients, agrochemicals, and irrigation in cropping systems (Andersen et al 2003;Lomba et al 2014;Benedetti 2017). Andersen et al (2003) defined three types of HNV farmland, and this categorization has been commonly followed.…”
Section: Introductionmentioning
confidence: 99%